Pavilion of women : a novel of life in the women's quarters - Buck, Pearl S. (Pearl Sydenstricker), 1892-1973 (Open Road Integrated Media, 2012)
From the author of The Good Earth comes the story of Madame Wu, a woman whose surprising decision to retire from married life and select a concubine for her husband upsets her extended household.